2009
DOI: 10.1177/0743558409350500
|View full text |Cite
|
Sign up to set email alerts
|

Renewal and Risk: The Dual Experience of Young Motherhood and Aging Out of the Child Welfare System

Abstract: This interpretive study examines how childhood history and the personal experience of being mothered impact the meaning attributed to motherhood among young mothers aging out of the child welfare system. Through the use of an interpretive approach, findings are derived from interviews with 15 females who reported an experience of pregnancy or parenting at the time of the interview. In the midst of the strain and challenge of motherhood, these young women report that motherhood has the potential to provide oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 43 publications
7
64
0
7
Order By: Relevance
“…drug taking). Pregnancy generated hope for the future (Chase et al, 2009;Schwerdtfeger & Wampler, 2009;Pryce & Samuels, 2010;O"Mahen et al, 2011). The responsibility of pregnancy was seen in a positive light, stimulating self-caring and protective behaviour (Armstrong & Pooley, 2005;Chase et al, 2009;Maxwell, Proctor & Hammond, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…drug taking). Pregnancy generated hope for the future (Chase et al, 2009;Schwerdtfeger & Wampler, 2009;Pryce & Samuels, 2010;O"Mahen et al, 2011). The responsibility of pregnancy was seen in a positive light, stimulating self-caring and protective behaviour (Armstrong & Pooley, 2005;Chase et al, 2009;Maxwell, Proctor & Hammond, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Youth acknowledged that there may be challenges associated with becoming a teen parent, but they largely minimized these challenges, had a positive view of relatives and friends who became parents at a young age, and believed that becoming a teen parent would not interfere with their education or more distal life goals. This further confirms qualitative findings by and others (e.g., Connolly, Heifetz, & Bohr, 2012;Constantine, Jerman, & Constantine, 2009;Knight, Chase, & Aggleton, 2006;Love et al, 2005;Pryce & Samuels, 2010) who have reported that youth with poor family attachment tend to feel ambivalent about becoming a teen parent. Although attitudes did not change, robust improvements in sexual health knowledge, and change in risky behaviors at follow-up is encouraging.…”
Section: Resultssupporting
confidence: 79%
“…Similarly, a subset of young mothers from the Midwest Study indicated developing a sense of purpose and belonging from their new emotional bond with their child, unlike anything experienced in relationships with their own parents or foster families. They saw themselves as valued, loved, and depended upon (Pryce & Samuels, 2010). Biological mothers frequently served as antirole models for young mothers out of foster care, for what not to do as a parent (Pryce & Samuels, 2010;Rolfe, 2008).…”
Section: Intangible Resources: Adult Identity and Negotiating The Pasmentioning
confidence: 99%
“…They saw themselves as valued, loved, and depended upon (Pryce & Samuels, 2010). Biological mothers frequently served as antirole models for young mothers out of foster care, for what not to do as a parent (Pryce & Samuels, 2010;Rolfe, 2008). These mothers also reported feeling pressure to "prove themselves" as good mothers, due to their childhood histories (Haight, Finet, Bamba, & Helton, 2009;Rolfe, 2008).…”
Section: Intangible Resources: Adult Identity and Negotiating The Pasmentioning
confidence: 99%